2022
DOI: 10.1128/spectrum.00849-22
|View full text |Cite
|
Sign up to set email alerts
|

Mutual Exclusion of Methanobrevibacter Species in the Human Gut Microbiota Facilitates Directed Cultivation of a Candidatus Methanobrevibacter Intestini Representative

Abstract: Methanogens are important hydrogen consumers in the gut and are associated with differing host health. Here, we determine the prevalence and abundance of archaeal species in the guts of a multi-ethnic cohort of healthy Singapore residents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 48 publications
0
3
1
Order By: Relevance
“…Upon closer examination of these networks, we found that M. smithii or Ca. M. intestini consistently co-occurred regardless of the age group, which was in contrast to previous findings based on Sanger sequencing (73). Additionally, the family Christensenellaceae was consistently associated with these archaeal species across all age groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Upon closer examination of these networks, we found that M. smithii or Ca. M. intestini consistently co-occurred regardless of the age group, which was in contrast to previous findings based on Sanger sequencing (73). Additionally, the family Christensenellaceae was consistently associated with these archaeal species across all age groups.…”
Section: Discussioncontrasting
confidence: 99%
“…Also, there is growing evidence showing the Erysipelatoclostridium plays in immune response, inflammation, and response to cancer immune therapy 44 . Methanobacteriaceae is the predominant methanogen in the human gut, and its presence or absence in the gastrointestinal tract has been linked to a variety of health characteristics, including changes in body weight and cardiovascular disease 45 .…”
Section: Discussionmentioning
confidence: 99%
“…7, P > 0.05). For detailed proteomic and metabolomic studies, this study focused on vesicles from Methanobrevibacter species, the most abundant archaea in the human gut microbiome, comprising up to 4% of the microbiome 86 . Methanobrevibacter species rely on syntrophic bacterial partners that provide small organic compounds like H 2 (or formate) and CO 2 for methanogenesis 63,87,88 .…”
Section: Discussionmentioning
confidence: 99%